Obesity or Overweight, a Chronic Inflammatory Status in Male Reproductive System, Leads to Mice and Human Subfertility - Fan, Weimin; Xu, Yali; Liu, Yue; Zhang, Zhengqing; Lu, Liming; Ding, Zhide (Frontiers in Physiology, 2018)
Obesity is frequently accompanied with chronic inflammation over the whole body and is always associated with symptoms that include those arising from metabolic and vascular alterations. On the other hand, the chronic inflammatory status in the male genital tract may directly impair spermatogenesis and is even associated with male subfertility. However, it is still unclear if the chronic inflammation induced by obesity damages spermatogenesis in the male genital tract. To address this question, we used a high fat diet (HFD) induced obese mouse model and recruited obese patients from the clinic. We detected increased levels of tumor necrosis factor (TNF-α) ，interleukin-6 (IL-6) and NOD-like receptor family pyrin domain containing-3 (NLRP3) in genital tract tissues including testis, epididymis, seminal vesicle, prostate and serum from obese mice. Meanwhile, the levels of immunoglobulin G (IgG) and corticosterone were significantly higher than those in the control group in serum. Moreover, signal factors regulated by TNF-α, i.e. p38, nuclear factor-κB (NF-κB), Jun N-terminal kinase (JNK), extracellular signal-regulated kinase (ERK) and their phosphorylated status, and inflammasome protein NLRP3 were expressed at higher levels in the testis. For overweight and obese male patients, the increased levels of TNF-α and IL-6 were also observed in their seminal plasma. Furthermore, there was a positive correlation between the TNF-α and IL-6 levels and BMI whereas they were inversely correlated with the sperm concentration and motility. In conclusion, impairment of male fertility may stem from a chronic inflammatory status in the male genital tract of obese individuals.